Photoisomerization of Mono-Arylated Indigo and Water-Induced Acceleration of Thermal cis-to-trans Isomerization - Huber, Ludwig A.; Mayer, Peter; Dube, Henry (Chemphotochem, 2018)
The front cover artwork is provided by Thomas Bartelmann and Henry Dube of the Department of Chemistry, Ludwig-Maximilians-Universität Munich (Germany). The image shows photoisomerization of mono-arylated indigo upon irradiation with red light. Read the full text of the Article at 10.1002/cptc.201700228.
CRIS-Team Scopus Importer:2023-03-07